Chiral luminescent CdS nano-tetrapods - GOVAN, JOSEPH; GOUNKO, IOURI (Royal Society of Chemistry, 2010)
The utilisation of chiral penicillamine stabilisers allowed the preparation of new water soluble white emitting CdS nano-tetrapods, which demonstrated circular dichroism in the band-edge region of the spectrum.
PUBLISHED
Keywords: Physical chemistry; chiral penicillamine stabilisers